Comparing spiritual development theory to homosexual identity development theory - Hinrichs, Diane (Kansas State University, 2009)
Maintaining identities of being a Christian and a lesbian or gay has traditionally in mainstream society been considered to be an oxymoron. Yet upon review, a large number of homosexuals profess to be Christians and find strength in their faith. The purpose of this report is create a hypothesis that is developed as a result of a literature review and informal interviews on the identity development and synthesis that occurs for lesbians and gays in the areas of homosexual identity and spiritual identity. To accomplish this task a comparison was made between Anthony D’Augelli’s Model of Lesbian, Gay, and Bisexual Development (1994) and Sharon Daloz Parks Spirituality Development Theory (1986, 2000). Within the confines of this report, key attention was paid to examining whether the developmental critical paths for each area can be visually constructed as parallel lines with independent critical paths occurring simultaneously, if there is only a one line with a singular critical path or if one critical path intersects the other and therefore certain development stage(s) of one model must be completed before the individual can progress in the other model. Findings revealed that in most cases individuals did not move simultaneously on the two developmental paths. Rather, it was necessary for most individuals to be high on either the spiritual identity development model or high on the homosexual identity development model in order to move forward on the other with the goal being to gain a reconciliation between the two identities.
Keywords: homosexual identity; spiritual identity; Education, Guidance and Counseling (0519)